Antiphospholipid syndrome associated with infections: clinical and microbiological characteristics of 100 patients. Issue 10 (10th September 2004) - Cervera, R; Asherson, R A; Acevedo, M L; Gómez-Puerta, J A; Espinosa, G; de la Red, G; Gil, V; Ramos-Casals, M; García-Carrasco, M; Ingelmo, M; Font, J
Abstract : Objective: To describe and analyse the clinical characteristics of 100 patients with antiphospholipid syndrome (APS) associated with infections. Methods: Patients were identified by a computer assisted search (Medline) of published reports to locate all cases of APS published in English, Spanish, and French from 1983 to 2003. The bilateral Fisher exact test was used for statistics. Results: 59 female and 41 male patients were identified (mean (SD) age, 32 (18) years (range 1 to 78)): 68 had primary APS, 27 had systemic lupus erythematosus, two had "lupus-like" syndrome, two had inflammatory bowel disease, and one had rheumatoid arthritis. APS presented as a catastrophic syndrome in 40% of cases. The main clinical manifestations of APS included: pulmonary involvement (39%), skin involvement (36%), and renal involvement (35%; nine with renal thrombotic microangiopathy, RTMA). The main associated infections and agents included skin infection (18%), HIV (17%), pneumonia (14%), hepatitis C (13%), and urinary tract infection (10%). Anticoagulation was used in 74%, steroids in 53%, intravenous immunoglobulins in 20%, cyclophosphamide in 12%, plasma exchange in 12%, and dialysis in 9.6%. Twenty three patients died following infections and thrombotic episodes (16 with catastrophic APS). Patients given steroids had a better prognosis (p = 0.024). The presence of RTMA and requirement for dialysis carried a worse prognosis (p = 0.001 and p = 0.035, respectively). Conclusions: Various different infections can be associated with thrombotic events in patients with APS, including the potentially lethal subset termed catastrophic APS. Aggressive treatment with anticoagulation, steroids, and appropriate antibiotic cover is necessary to improve the prognosis.